Fermentation of mucin and plant polysaccharides by strains of Bacteroides from the human colon. - Salyers, A A (1977)
Ten Bacteroides species found in the human colon were surveyed for their ability to ferment mucins and plant polysaccharides ("dietary fiber"). A number of strains fermented mucopolysaccharides (heparin, hyaluronate, and chondroitin sulfate) and ovomucoid. Only 3 of the 188 strains tested fermented beef submaxillary mucin, and none fermented porcine gastric mucin. Many of the Bacteroides strains tested were also able to ferment a variety of plant polysaccharides, including amylose, dextran, pectin, gum tragacanth, gum guar, larch arabinogalactan, alginate, and laminarin. Some plant polysaccharides such as gum arabic, gum karaya, gum ghatti and fucoidan, were not utilized by any of the strains tested. The ability to utilize mucins and plant polysaccharides varied considerably among the Bacteroides species tested.